2009
DOI: 10.1002/ajhb.20920
|View full text |Cite
|
Sign up to set email alerts
|

Variations in male parenting behavior and physiology in the common marmoset

Abstract: Infant survival and wellbeing is dependent upon good parenting skills. In some species of primates, fathers are necessary to ensure both positive developmental and social outcomes for their offspring. Common marmosets and the related cotton-top tamarin monkeys provide extensive paternal care of multiple offspring and are essential for infant survival. However, we have found significant variation in a father’s motivation to respond to infant stimuli. Additionally, marmoset males who are experienced fathers are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 24 publications
(27 reference statements)
2
14
0
Order By: Relevance
“…For example, Dixson and George [1982] not only found a reciprocal relationship between testosterone and prolactin in C. jacchus, but they also discovered that males had lower testosterone concentrations after infant carrying. Also in C. jacchus, Prudom et al [2008] and Ziegler et al [2009aZiegler et al [ , 2011 found a similar relationship between lower testosterone concentrations in fathers and direct infant stimuli. Similarly, in C. kuhlii, Nunes et al [2000Nunes et al [ , 2001 found that testosterone concentrations were lower among males who carried infants at high rates than males who carried infants at low rates.…”
Section: Introductionsupporting
confidence: 61%
See 3 more Smart Citations
“…For example, Dixson and George [1982] not only found a reciprocal relationship between testosterone and prolactin in C. jacchus, but they also discovered that males had lower testosterone concentrations after infant carrying. Also in C. jacchus, Prudom et al [2008] and Ziegler et al [2009aZiegler et al [ , 2011 found a similar relationship between lower testosterone concentrations in fathers and direct infant stimuli. Similarly, in C. kuhlii, Nunes et al [2000Nunes et al [ , 2001 found that testosterone concentrations were lower among males who carried infants at high rates than males who carried infants at low rates.…”
Section: Introductionsupporting
confidence: 61%
“…Prudom et al [2008] and Ziegler et al [2009aZiegler et al [ , 2011 found that fathers demonstrate lower testosterone concentrations following direct stimuli from an infant. Similarly, Dixson and George [1982] discovered that males had lower testosterone concentrations after they had carried infants.…”
Section: Father-infant Proximity and Fam Concentrations Over The Postmentioning
confidence: 96%
See 2 more Smart Citations
“…For example, the in fl uence of hormones like prolactin, vasopressin, oxytocin, and testosterone in relation to bonding and infant care, or behavioral trade-offs between care and mate-acquisition have been extensively studied, even if still not completely understood (Bales et al 2004 ;Brockmann et al 2001 ;Gettler et al 2011 ;Goymann et al 2007 ;Gray et al 2007 ;Hirschenhauser and Oliveira 2006 ;Huck et al 2005 ;Schradin and Anzenberger 2002 ;Schradin et al 2003 ;Trainor andMarler 2001, 2002 ;Wing fi eld et al 1990 ;Ziegler 2000 ;Ziegler et al 1996Ziegler et al , 2000 . Differences in hormone production, responsiveness, or ontogenetic exposure may partly explain individual differences in caretaking behavior (Birnie et al 2011 ;Drea 2007 ;Ziegler et al 2009 ) . Other in fl uential factors include the rank, age and previous experience of the caretaker, sex of the infant, group size and composition, relatedness between caretaker and infant or mother, season of conception, or predation risk (Anderson 1992 ;Bercovitch 2002 ;Hoage 1977 ;McGrew 1988 ;O'Brien and Robinson 1991 ;Pryce 1988 ) .…”
Section: Proximate Perspectives Of Parental Carementioning
confidence: 99%